A 41-marker 37-color full spectrum flow cytometry panel for the deep immunophenotyping of human peripheral and liver natural killer cells - Paul, Alberta Gerarda Antonia; Reichel, Konrad H. H.; Garcia-Vallejo, Juan J.; Heij, Lara R.; Jaimes, Maria C.; Kharraz, Yacine (Frontiers in Immunology, 2025)
Natural killer cells (NK cells) are granular lymphocytes with cytotoxic activity that have a role in both innate and adaptive immune responses. NK cells consist of a diverse array of phenotypes with specific functions imposed by the microenvironment. Liver NK cells are an abundant lymphocyte population playing a key role in tuning immune responses under physiological and pathological conditions. For example, NK cell functional and phenotypic changes occur during liver cancer progression and correlate with disease prognosis. As liver cancer has the second-highest mortality rate among solid cancers, it is important to define the composition and the dynamics of the liver and peripheral NK cell compartment both in health and disease state. In-depth analysis of the phenotypes and functional status of NK cells and their frequencies will expand our knowledge on their role in maintaining immune tolerance, disease progression, and aid the development of novel treatments. We present here a 41-marker 37-color spectral flow cytometry panel for the in-depth phenotyping of human peripheral and liver NK cells. This paper describes the first spectral flow cytometry panel with 35 markers potentially co-expressed on one cell type (NK cells) including the panel design process, sample preparation, staining protocol, quality control metrics, acquisition protocol and workflows to analyze NK cells in the periphery and liver. NK cell subsets and phenotypes were distinguished by including markers of differentiation, maturation, tissue residency, migratory potential, functional status, key transcription factors, and immune checkpoint molecules. Liver-type ILC1s (Lt-ILC1s) could be identified by inclusion of additional markers and modification of published gating strategies. Furthermore, we describe the dynamics of peripheral and liver NK cells. Finally, we show the validity of markers included to indicate NK cell dysfunction in samples of patients with Hepatocellular Carcinoma (HCC). This high parameter high resolution panel provides a key tool for in-depth delineation of distinct NK cell subsets in the periphery and in liver, in health and disease state. It allows for the robust identification of NK cells subsets with low frequencies and can effectively be used for samples with limited cell numbers.